Pengujian Daya Hasil dan Ketahanan Penyakit Hawar Daun Bakteri Tanaman Padi Hibrida - Lopes Hornai, Ermelinda Maria; Purwoko, Bambang Sapta; Suwarno, Willy Bayuardi; Dewi, dan Iswari Saraswati (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTHybrid rice varieties  is an alternative technology to improve  productivity of low land rice. The results of previous studies have identified and found the male sterile lines Wild Abortive type and Kalinga are resistant to bacterial leaf blight pathotype III, IV and VIII. The objectives of the research were to obtain information on agronomic characters, yield evaluation, genetic parameters, and repeatability information. The experiment was conducted in two locations namely  Muara and Indramayu experimental stations. The design used was a Randomized Complete Block Design with three replication at each site.  Each replicate consisted of 17 hybrid rice and three check varieties. The results from locations showed that genotype BI485A/BP1 (IR53942) has the highest yield of 5.8 ton ha-1. The coefficient of genetic and phenotypic diversity of six agronomic characters was low. The repeatability for seven character observed were low, except for days to flowering. The  scoring value  of bacterial leaf blight disease in Indramayu showed that nine genotypes exhibit resistance.Keywords: cytoplasmic male sterile lines, disease resistance